Attitudes towards chiropractic: an analysis of written comments from a survey of north american orthopaedic surgeons - Busse Jason W; Jim Janey; Jacobs Craig; Ngo Trung; Rodine Robert; Torrance David; Kulkarni Abhaya V; Petrisor Brad; Drew Brian; Bhandari Mohit (Chiropractic & Manual Therapies, 2011)
Abstract Background There is increasing interest by chiropractors in North America regarding integration into mainstream healthcare; however, there is limited information about attitudes towards the profession among conventional healthcare providers, including orthopaedic surgeons. Methods We administered a 43-item cross-sectional survey to 1000 Canadian and American orthopaedic surgeons that inquired about demographic variables and their attitudes towards chiropractic. Our survey included an option for respondants to include written comments, and our present analysis is restricted to these comments. Two reviewers, independantly and in duplicate, coded all written comments using thematic analysis. Results 487 surgeons completed the survey (response rate 49%), and 174 provided written comments. Our analysis revealed 8 themes and 24 sub-themes represented in surgeons' comments. Reported themes were: variability amongst chiropractors (n = 55); concerns with chiropractic treatment (n = 54); areas where chiropractic is perceived as effective (n = 43); unethical behavior (n = 43); patient interaction (n = 36); the scientific basis of chiropractic (n = 26); personal experiences with chiropractic (n = 21); and chiropractic training (n = 18). Common sub-themes endorsed by surgeon's were diversity within the chiropractic profession as a barrier to increased interprofessional collaboration, endorsement for chiropractic treatment of musculoskeletal complaints, criticism for treatment of non-musculoskeletal complaints, and concern over whether chiropractic care was evidence-based. Conclusions Our analysis identified a number of issues that will have to be considered by the chiropractic profession as part of its efforts to further integrate chiropractic into mainstream healthcare.